APLIKASI MENJADI MODEL PENGEMBANGAN DALAM PEMBELAJARAN OLAHRAGA: LITERATURE REVIEW FORM PROCESSING DATA - Aldiansyah, Aldiansyah; Irawan, Muhammad Farid; Rahmawati, Nurul; Nugraha, Ganjar; Femia, Femia (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2023)
Learning sports using a development model such as an application, really provides an advantage in terms of delivering material more practically and effectively. In addition, it can alleviate a sports activity that is usually carried out outdoors to stay indoors. The purpose of this study, to find out the Application as a model in sports learning in the current era that is relevant and widely used. The method used is qualitative in the form of a systematic review, which will examine or review a journal that is in accordance with the problem, so that it becomes evidence and becomes a consideration for the results of this study. Then it will take the form of data processing with aspects and categories in the content analysis of each journal, including (1). Type of research, (2). Research subjects, and (3) results, which will get results in accordance with the 3 specified aspects. The results of this study found that the type of research most widely used in the development model is R&D (Research and Development), then the research subject who is the target in the sports learning process takes place, namely high school students. And an effective and flexible development model in sports learning in this era is the application, which has become the initial purpose of this research to find out this. These results are in accordance with the aspects and categories that have been determined by processing data from the 24 journals reviewed.